Integrating Virtual Reality With Activity Management for the Treatment of Fibromyalgia: Acceptability and Preliminary Efficacy. Issue 6 (June 2015) - Garcia-Palacios, Azucena; Herrero, Rocio; Vizcaíno, Yolanda; Belmonte, Miguel A.; Castilla, Diana; Molinari, Guadalupe; Baños, Rosa Maria; Botella, Cristina
Abstract : Objectives: Cognitive-behavioral therapies (CBT) for fibromyalgia syndrome (FMS) are important interventions in the management of this condition. Empirical evidence reports that although the results are promising, further research is needed to respond more appropriately to these patients. This study focuses on exploring the use of Virtual Reality (VR) as an adjunct to the activity management component. The aim of this study is to present the results of a small-sized randomized controlled trial to test the preliminary efficacy and acceptability of this component. Materials and Methods: The final sample was composed of 61 women diagnosed with FMS according to the American College of Rheumatology. The sample was randomly allocated to 2 conditions: VR treatment and treatment as usual. Results: Participants in the VR condition achieved significant improvements in the primary outcome: disability measured with the FIQ. The improvement was also significant in secondary outcomes, such as perceived quality of life and some of the coping strategies included in the Chronic Pain Coping Inventory: task persistence and exercise. There were no differences in other secondary outcome measures like pain intensity and interference and depression. Participants reported high satisfaction with the VR component. Discussion: The effects were related to the psychological aspects targeted in the treatment. The component was well accepted by FMS patients referred from a public hospital. These findings show that the VR component could be useful in the CBT treatment of FMS and encourage us to continue exploring the use of integrating VR with CBT interventions for the treatment of FMS.